Fish hatchery management - Piper, Robert G. (U.S. Department of the Interior, Fish and Wildlife Service, 1982)
This book is aimed more for hatcheries that are raising Trout, Salmon, Catfish and other food fishes. However, there is information in this book that even ornamental fish hatcheries will find an incredible amount of useful information, includes the Fish Nutrition.